BS EN IEC 61753-022-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 022-02. Multimode fibre optic connectors terminated as pigtails and patchcords for category C. Controlled environment (2nd August 2023) - British Standards Institution,
No abstract available